Module based on wavelet-transform for electromyography signals processing - Hamad Shejoon Hamed (Boston, USA, 2020)
In developed software optimal EMG resolution component (sub-signal) was selected, and then the reconstruction of the useful information signal was done. Noise and unwanted EMG parts were eliminated throughout this process. Developed module consists of 5 main units for EMG processing based on wavelet-transform. The obtained results allow in the automated mode of developed module execute processing and analysis EMG signals for classification data.
Keywords: EMG; processing; wavelet-transform; programed module; automated mode